2014
DOI: 10.1093/bja/aet435
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of gastric content during labour under epidural analgesia: a prospective cohort study

Abstract: Bedside ultrasonographic antral CSA measurement is feasible in pregnant women during labour and easy to perform. The observed decrease in antral CSA during labour suggests that gastric motility is preserved under epidural anaesthesia. The procedure could be used to assess individual risk of gastric content aspiration during labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 15 publications
3
46
2
Order By: Relevance
“…40 Several authors have studied quantitative gastric US in the obstetric population. 33,34,[43][44][45] Most have focused on defining cutoff values for the gastric antral area that would allow rapid differentiation between varying levels of aspiration risk. For instance, Jay et al 44 reported that using Bouvet's model, a gastric antral area of less than 381 mm 2 in the supine position is 81% sensitive and 76% specific to identify a grade 0 antrum.…”
Section: Evaluation Of the Obstetric Patientmentioning
confidence: 99%
“…40 Several authors have studied quantitative gastric US in the obstetric population. 33,34,[43][44][45] Most have focused on defining cutoff values for the gastric antral area that would allow rapid differentiation between varying levels of aspiration risk. For instance, Jay et al 44 reported that using Bouvet's model, a gastric antral area of less than 381 mm 2 in the supine position is 81% sensitive and 76% specific to identify a grade 0 antrum.…”
Section: Evaluation Of the Obstetric Patientmentioning
confidence: 99%
“…52,53) Several mathematical models have been used to assess different patient positions and clinical scenarios. [54][55][56][57] A study by Bouvet 44) used the antral cross-sectional area with cut-off values measured in a 45° semi-recumbent position. CSAs > 3.4 cm 2 and > 3.8 cm 2 were reported in non-pregnant and pregnant patients, respectively, and these values correlated with a gastric volume > 0.8 ml kg − 1 .…”
Section: Gastric Contents and Gastric Emptyingmentioning
confidence: 99%
“…Bataille et al 54) determined the cut-off value corresponding to increased gastric content by ultrasound measurement of antral CSA in non-laboring women in their third trimester. Ultrasound was performed before and after the intake of a non-clear fluid, followed by two antral CSA measurements on parturients who were in spontaneous labor during catheter placement for epidural analgesia and at full cervical dilatation.…”
Section: Gastric Contents and Gastric Emptyingmentioning
confidence: 99%
“…Administration can be initiated the evening before surgery in elective cases. Recent studies have suggested that the use of bedside gastric ultrasonography can be useful in assessing gastric contents during labor49 and prior to elective cesarean delivery 50…”
Section: Technical Considerationsmentioning
confidence: 99%